Sub-leading twist transverse momentum dependent parton distributions in the light-front quark-diquark model - Shubham Sharma; Narinder Kumar; Harleen Dahiya (Nuclear Physics B, 2023)
In this study, the T-even sub-leading twist transverse momentum dependent distributions (TMDs) of proton in the light-front quark-diquark model (LFQDM) have been investigated. We have derived the overlap form of the light-front wave functions (LFWFs) for the sub-leading twist proton TMDs by detangling the un-integrated quark-quark correlator for the semi-inclusive deep inelastic scattering (SIDIS). We have obtained the explicit expressions of TMDs for both the cases of the diquark being a scalar or a vector and analyzed their relationships with leading twist TMDs within the same model. Average transverse momenta and average square transverse momenta for the TMDs have been tabulated and compared with the results from the light-front bag model and the light-front constituent quark model (LFCQM). In addition to this, we have also compared our results for the PDF e(x) with the recent CLAS collaboration results.Transverse momentum dependent parton distributions of proton; T-even sub-leading twist TMDs; light-front quark-diquark model.